Antecedents of online product recommendation continuous usage intention / Muhammad Ashraf - Muhammad , Ashraf (2016)
Immense product choices, the complexity, and enormous amount of information available on business to consumer (B2C) e-commerce site challenge customers’ limited information processing capabilities, and identifying a product which fits their need is not an easy job. There is also consumers’ dilemma of wanting to have more information on the one hand and being overloaded with too much information on the other hand. Therefore, to help consumers deal with this dilemma, e-retailers are increasingly equipping their e-commerce sites with distinct product recommender systems to provide highly personalized product recommendations, and assistance in searching, comparing, and evaluating product information. The online product recommendation (OPR) also consisting of past consumer recommendations in the form of product ratings and reviews, which pursued the customers to buy recommended products. It subsequently can be resulted in higher consumer spending and improved retention rate. However, drawing benefits out of these advantages depends on whether and to what extent consumers embrace and fully utilise OPR. The current percentage of Amazon sales based on OPR usage indicated that a large proportion of online consumers are not using OPR for their online buying decision given the fact that they have not yet developed trust in OPR. Nevertheless, no matter how useful OPR is, a critical issue is whether consumers accept and continue OPR use. This is an important yet neglected issue in existing OPR research. Therefore, the current study develops an integrated research model to investigate salient determinants of OPR continuous usage intention and to understand how they influence the dependent variable. With regards to that, this study specifies four research issues. First, to identify the factors that can be used as surrogate measure of OPR performance in terms of OPR usage outcomes. Second, to identify the factors that measure the consumers’ OPR evaluation beliefs in terms of their instrumental, social-psychological, and affective beliefs. Third, to ascertain how the consumers’ perception of OPR performance influences their behavioural intention towards OPR continuous usage. Fourth, to examine the impact of OPR evaluation factors on consumers’ perception of OPR performance. However, four theoretical models; IS continuance model, effort-accuracy model, theory of trust formation, and flow theory, were adopted and integrated to describe the causal linkages between the determinants of OPR performance and OPR continuous usage intention. Subsequently, six main hypotheses were developed and tested based on the integrated research model. A questionnaire that reflects the research constructs is developed to collect the primary data for this study. The data were collected from 626 Amazon customers who have used OPR for their buying decision over at least six months. Since this study is quantitative with a deductive approach, it employs Partial Least Squares-Structural Equation Modelling (PLS-SEM) to validate and confirm research model by testing the relationships that were hypothesized. The findings of this study provide empirical evidences on the salient determinants of OPR continuous usage intention. The PLS results showed that all evaluation factors (i.e. ease of use, usefulness, confirmation, trust, and enjoyment) have statistically proven significant impact on OPR performance, except perceived ease of use. Furthermore, the study findings approve the influence of OPR performance on consumers’ OPR continuous usage intention for future buying decision. The findings indicated that consumers’ perceived decision effort, decision quality, and satisfaction representing OPR performance are direct determinants of OPR continuous usage intention and indirect measure of actual OPR continuous usage behaviours. Finally, research implications, limitations, and future researches are highlighted.